Comparative Study on the Variability Margin of Concrete Strength between Weight and Volume Batching Methods - Yahya, Ismail Akolawole; Abubakar, Abdulhameed Umar; Mohammed, Yusuf Hassan; Usman, Suleman Yusuf (ABUAD Journal of Engineering Research and Development (AJERD), 2025)
Variability of strength in concrete has significant effect on the structural integrity, safety and performance of every concrete structure. It is a valid concern which defies any mix design method, but depends changes in material, production process and environmental condition. The aim of this study is to determine the effect of the batching method on the margin of variability of concrete strength. Methods of batching by weight and volume were considered for three popular nominal mix proportions including 1:2:4, 1:1.5:3 and 1:1:2. The standard deviation of the 28th day compressive strength was determined and analysed for quantitative and qualitative assessment of concrete quality. The result indicates that lower water/cement ratio recorded higher compressive strength for the same mix proportions under both weight and volume batched method. The three mixes of ratios 1:2:4, 1:1.5:3 and 1:1:2 that were weight batched outperform the volume batch of the same mix ratios in compressive strength by 33.8%, 14.5% and 24.9% respectively. It was concluded that volume batched mixes may only be considered for on – site concrete construction when water/cement ratio can be strictly controlled or stiff mixes are applicable as well as characteristic strength of concrete is below 25N/mm2. Where these conditions cannot be met, batching by weight with controlled water/cement ratio should be considered for on – site concrete construction. This study recommended the development of mix design template suitable for volume batched mixes considering several factors promoting variability in concrete strength, through the collective efforts of researchers, site engineers and regulatory bodies.